Berlin: Economic and Spatial Change - Martin Gornig; Hartmut Häussermann (European Urban and Regional Studies, 2002)
This paper discusses the past and future economic situation of Berlin in the German city system. Comparing the shares of employment in various service sectors of total employment in Germany from 1939 to 1997 shows the significant changes in the role as a metropolis. Berlin has lost its dominant position as a consequence of isolation from international development for 40 years. Despite successful expansion and restructuring processes in superregionally oriented services, Berlin is still behind the West German economic centers. Future-oriented perspectives for Berlin cannot be found in a regaining of lost functions, but in developing new fields of international service functions. Berlin's potential therefore is its cultural diversity as a context for productive innovations.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. - This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330